DESAIN TEKNOLOGI APE: FLANELEVAYA KNIGA UNTUK PEMBELAJARAN ANAK USIA DINI ERA NEW NORMAL - Nurmalina Nurmalina (Universitas Pahlawan Tuanku Tambusai, 2021)
Parents have limited ways, knowledge, and educational game tools that can help them to guide their children in learning. This Community Service activity aims to provide training on the design of APE technology: flanelevaya kniga for early childhood learning. The method of this community service activity uses the lecture method, demonstration, question and answer method and practice group guidance for early childhood. The result of this service is that entrepreneurs of Educational Game Equipment for Early Childhood in Sungai Pinang Village need an understanding of the importance of quality APE, provide entrepreneurs with the ability to develop Flaga with the aim of helping them achieve marketing targets, this training provides the right solution for entrepreneurs' problems in running a business.